2019
DOI: 10.3389/fimmu.2019.00528
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Evolution Intersects With Host Tolerance

Abstract: Over the past 200 years, tuberculosis (TB) has caused more deaths than any other infectious disease, likely infecting more people than it has at any other time in human history. Mycobacterium tuberculosis ( Mtb ), the etiologic agent of TB, is an obligate human pathogen that has evolved through the millennia to become an archetypal human-adapted pathogen. This review focuses on the evolutionary framework by which Mtb emerged as a specialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 181 publications
(199 reference statements)
0
31
0
1
Order By: Relevance
“…What is clear is the evidence for the higher dissemination ability of "modern" lineages compared with "ancient" ones 21 . The fact that the latter are restricted to specific geographical regions also points to some sort of genetic susceptibility linked to race/ethnic groups, as proposed by several authors 7,17,66 . Our model has not considered this aspect.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…What is clear is the evidence for the higher dissemination ability of "modern" lineages compared with "ancient" ones 21 . The fact that the latter are restricted to specific geographical regions also points to some sort of genetic susceptibility linked to race/ethnic groups, as proposed by several authors 7,17,66 . Our model has not considered this aspect.…”
Section: Discussionmentioning
confidence: 84%
“…Portevin et al 16 compared the innate response triggered in macrophages and dendritic cells by different strains from both lineages and concluded that "ancient" ones induce a higher pro-inflammatory profile when infecting macrophages and dendritic cells. These results have been interpreted as a virulence/ immune response trade-off for "ancient" strains as bacilli are discovered early by the immune system and have less chance to progress, including extrapulmonary dissemination, which contrasts with the situation found for modern strains 17 . However, the current interpretation does not include this trade-off as this pro-inflammatory profile can, in fact, enhance the infiltration of neutrophils into Mtb-infected lesions, thus resulting in a better chance to quickly progress to active TB 18 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Mycobacterium tuberculosis (Mtb) has coevolved with humans for 70,000 years 28. Unlike the opportunistically parasitic and the non-pathogenic soil dwellers species of mycobacteria, Mtb has no known environmental reservoirs and does not survive outside human hosts pointing to its highly specialized nature 29. Interestingly, 90–95% of infected individuals (9 out of 10 people) are resilient or tolerant to the presence of Mtb without any disease symptoms 30.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium tuberculosis (Mtb) has become highly adapted to its human host, as it spread globally along with human migrations over tens of thousands of years (3,4). As much as one-third of the human population has been exposed to Mtb, which causes a persistent infection than can last for years, or even decades, despite a robust immune response that eradicates less pathogenic mycobacteria (5).…”
Section: Introductionmentioning
confidence: 99%